Profile of Critical Thinking Ability of High School Students on Animalia Material During Hybrid Learning in the Pandemic Era - Andri Tri Nugroho; Puguh Karyanto; Bowo Sugiharto (Jurnal Penelitian Pendidikan IPA, 2022)
The spread of the Covid-19 virus has brought changes in various sectors including education. Various policies have also been implemented in schools, such as distance learning to face-to-face learning on a limited basis. 21st century skills emphasize the creation of students who are able to apply technology in the digital era, think creatively and think critically. This study aims to determine the critical thinking skills needs of high school students in class X during the pandemic, especially on animalia material. The subjects of this study were high school students in class X in the province of Central Java, which was carried out using a random sampling technique. This research is quantitative research using a questionnaire sheet via google form consisting of 10 critical thinking questions. The instrument test was tested for validity and reliability using RASCH model with the Winsteps 3.73 application. The results of this study indicate that students' critical thinking skills are still low and further research is needed to improve students' critical thinking skills